PENGARUH PERSEPSI TENTANG PERUBAHAN ORGANISASI DAN EFIKASI DIRI TERHADAP MOTIVASI KERJA KARYAWANSebuah Studi Kasus di Badan SAR Nasional - , Agus Haryono ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The National SAR Agency (Basarnas) as the government body responsible for providing search and rescue services in Indonesia has come to a new era since 2008, it is no more structurally subordinate to Ministry of Transport but directly subordinate to the President of Republic of Indonesia. This basic organization change get various responses from its employees related to the influences/impacts arising from the organization and self-efficacy changes on the improvement of job performance and employeesâ welfare. Related to the issue, this research is designed to know the influence of perception on organization and self-efficacy changes towards working motivation of the National SAR Agencyâs employees. This research employs survey method by involving samples of 100 persons taken by simple random sampling. Data collection uses Likert Scale questionnaire that is previously tested for its validity and reliability. The data, then, is analyzed by employing correlation and regression. The results of research shows that perception on the organization change gives positive and significant influence on the employeesâ working motivation. The positive influence occurs for the organization change gives better expectation for the need and satisfaction fulfillment of the individual, both from carrier improvement side, self-actualization and their welfare that encourages them to work maximally for their organization. Self-efficacy also shows positive influence on the employeesâ working motivation. This positive influence occurs for selfefication could provide strong self confident for an individual to complete any task or job, so that, it emerges optimism encouraging employees to always work hard. Simultaneously, the perception on organization change and self-efficacy also have positive and significant influence on the employeesâ working motivation. Based on the results of this research, it is necessary to create a clear planning in the form of blue print for the change direction performed by organization and to be socialized to the employees. The leader has to be able to make the employees believe that the change being performed is a positive change that providing positive expectations for the employees. In addition, it is also necessary to improve employeesâ competencies and skills in doing their jobs to enhance their self-efficacy through the job training provision.